Key breeding sites of Aedes mosquitoes in Huaylau village, Pakse city, Champasack province, Lao People Democratic Republic 2019 - Le Thi Thanh, Huong; Nguyen Quynh, Anh; Vanhnasack, Saenthavisouk; Vu Sinh, Nam (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Objectives: The elimination of key breeding sites of dengue vector is applied worldwide to control the vector density under the critical epidemic threshold. This study aimed to identify key breeding sites of Aedes mosquitos and associated factors in Huaylau village, Pakse city, Champasack province in Laos in 2019.Methods: This was a cross-sectional study, combining of immature stage survey of Aedes mosquitoes in all water and discarded containers and the community’s knowledge and practices on the prevention of dengue fever in all 240 households in Huaylau village. Multivariate logistic regression was applied to identify factors associated with the absence of Aedes larvae and pupae in the village. Statistical significance was set at a p-value less than 0.05.Results: Among the 720 water and discarded containers surveyed, the study found 654 Aedes larvae and pupae; of which 94.6% were immature Aedes aegypti. Key breeding sites of Aedes aegypti included water jars (34.2%), plastic drums (30.7%), tanks < 500 litter (14.7%), and discarded containers (12.6%), while that of all Aedes albopictus was discarded containers. The community’s better practices on the prevention of dengue fever contributed to the increased odds of the absence of Aedes larvae ad pupae by 1.612 (95%CI: 1.218-2.134, p
Keywords: key breeding sites; Aedes; mosquito; pupae; larvae; Champasack province